Public Theology as cultivation of a common public life - Bezuidenhout, RM; Naudé, PJ (Nederduitse Gereformeerde Teologiese Tydskrif, 2010)
This is paper is an exposition of “public theology” according to three criteria for such a theology developed by American theologian, Linell Cady. The criteria she sets for a public theology is: An open form of argumentation, an accessible style of communication, and a focus on contemporary issues of public concern. This is the basis on which Cady reconstructs theo-logy in terms of God the Creator, Sustainer and Redeemer.